Fault-Tolerant Resilient Control For Fuzzy Fractional Order Systems - Sakthivel, Rathinasamy; Ahn, Choon Ki; Joby, Maya (IEEE transactions on systems, man, and cybernetics. Systems, 2019)
This paper investigates the problem of resilient fault-tolerant control for a class of Takagi-Sugeno fuzzy model which is described by fractional order differential equations. In particular, the system input under consideration is subject to actuator saturations, actuator faults, and nonlinearities. The main purpose of this paper is to put forward a generalized nonlinear resilient fault-tolerant controller that can make the considered system robustly asymptotically stable. Utilizing the concept of continuous frequency distribution, a new set of linear matrix inequalities, which are the sufficient conditions for robust asymptotic stability of the closed-loop system, are derived by using the indirect Lyapunov approach. Two numerical examples are included to illustrate the feasibility and effectiveness of the proposed method.